A Study on the Seed Morphology of the Genus Cassia L. sensu lato in the Sudan* - Abdalla, Wail E.; El Ghazali , Gamal E. B.; N. Guma’a, Abdelgabbar; Khalid, Hassan E. (University of Khartoum Journal of Agricultural Sciences, 2025)
Morphological characters of seeds from 23 Cassia L. sensu lato species from Sudan were examined with the aid of Stereo Microscope in order to clarify their taxonomic status. The seeds of all members of the genus Senna (with the exception of S. bicapsularis) were areolate, whereas the seeds of Cassia sensu stricto and Chamaecrista species were not areolate and the shapes of the latter two genera were ovate-elliptic and rhombic, respectively. The seeds are described, an indented identification key is presented, and the unique taxonomic position of S. bicapsularis is discussed. The results supported the division of the genus Cassia L. sensu lato into three allied genera (Cassia sensu stricto, Chamaecrista and Senna).